BILINGUAL AND REGULAR CLASS STUDENTS’ ATTITUDES TOWARDS ENGLISH - Nihta Liando (LITERA, 2012)
This article presents the results of the study investigating the relationship between the students’ attitudes towards English and their English achievements in bilingual and regular classes and investigating the differences. The study was conducted in a junior high school in Manado. There are 30 Year VIII students in each bilingual class and each regular class. The results are as follows. First, there is a significant correlation between the students’ attitudes towards English and their achievements. Second, there is a significant difference in their English achievements between bilingual class students and regular students. Third, female students have higher English achievements than male students. Bilingual class students have more positive attitudes and higher English learning achievements than regular class students.